Diet formulation techniques and lysine requirements of 1-to 22-day-old broilers - Siqueira, J. C. [UNESP]; Sakomura, N. K. [UNESP]; Dourado, L. R. B.; Ezequiel, J. M. B. [UNESP]; Barbosa, N. A. A.; Fernandes, J. B. K. [UNESP] (Facta-fundacio Arnco Ciência Tecnologia Avicolas, 2013)
Two experiments were carried out to compare two techniques (amino acid supplementation and dilution) for formulating experimental diets for pre-starter (1 to 8 days) and starter (8 to 22 days) broiler chicks and to estimate digestible lysine requirements using the dose-response method. In each experiment, 1,200 male Cobb 500 chickens were randomly distributed according to a 5x2 factorial arrangement (lysine level x formulation technique) with six replicates of 20 birds each. For the supplemented diet, a basal diet was formulated to meet the nutritional requirements, then L-lysine HCl was added to achieve digestible lysine levels of 0.975, 1.082, 1.189, 1.296 and 1.403% in the pre-starter diets and 0.840, 0.932, 1.024, 1.116 and 1.208% in the starter diets. For the diluted diet, a diet high in crude protein (CP) and relatively low in lysine was formulated and to which was added a protein-free diet until lysine levels were similar to those described above for the supplemented diet. The results suggest that the dilution technique favored the performance potential and better met lysine requirements compared with the supplementation technique. Lysine levels required for optimal feed conversion ratio of broilers during the pre-starter and starter phases were estimated at 1.361 and 1.187%, which are equivalent to lysine intake of 0.340 and 0.797 g/day, respectively.
Keywords: Broilers; Diet formulation; Dose-response; Lysine; Performance